PENGARUH SIKAP KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP PEMBELAJARAN ORGANISASI DALAM MENINGKATKAN KINERJA BISNIS - Hendi Eka Sumarga; Dudung Hadiwijaya (Universitas Muhammadiyah Tangerang, 2018)
The Small and Medium Enterprises (SMEs) sector has proven resilient, when the economic crisis in 1998, only the SME sector survived the collapse of the economy, while the larger sector fell by the crisis. The Role of Small and Medium Enterprises (SMEs) as an economic movement, its existence is the engine of growth for the growth and development of new entrepreneurs and the increasing performance of SMEs. However, SMEs still face obstacles in terms of technical expertise, competence, entrepreneurship and management as well. Furthermore, the problem faced is limited access to productive resources such as raw materials, capital, technology, market facilities and information. The purpose of this study was to analyze the influence of entrepreneurial attitudes and market orientation on learning in improving business performance of SMEs themselves. This research model consists of three hypotheses with four variables namely entrepreneurial attitude, market orientation and organizational learning on business performance. The data used is 82 SMEs in Tangerang City using the Structural Equation Modeling analysis tool in the Smart PLS program. The results of data analysis prove that all proposed hypotheses can be accepted. So it can be concluded that business performance is influenced by three factors, both directly and indirectly, namely organizational orientation, market orientation and entrepreneurial attitudes.